The Effect of the Role Playing Method on Reading Aloud Skills in Indonesian Class 1 Subjects at SD Negeri Condong Tasikmalaya - indah sari rohaeti; Sunanih Sunanih; Yopa Taufik Saleh (Buana Pendidikan, 2021)
The background of this research is that the value of reading aloud skills in Indonesian class 1 subjects in elementary school is still low, it is necessary to update in improving student learning outcomes and teacher creativity in managing the learning process. This study aims to determine the effect of the Role Playing method on students' reading skills in Indonesian class I subjects at SD Negeri Condong Tasikmalaya. This research is a pre-experimental design type one-group pretest-posttest design. ). The subjects in this study were all 1st grade students at SDN Condong Tasikmalaya, totaling 36 students consisting of 14 girls and 22 boys. Based on the results of the calculation research and data analysis of the measurement results, it can be concluded that: The role playing method has a significant effect on improving students' reading skills at SDN Condong Tasikmalaya. This is indicated by the results of the initial test and the final test of reading aloud skills in the Indonesian language subject which has a greater and significant effect with the result of t arithmetic being greater than t table (6.90 > 1.70) which means that the role playing method has a significant effect. significant effect on the aloud reading skills of the first grade Indonesian students at SDN Condong Tasikmalaya.